PENGARUH AGRESIVITAS PAJAK TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TEKNOLOGI DAN DIGITAL DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Syathira, Idsa Salwa; Juniartika, Suci; Anam, Muhammad Khairul (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effect of tax aggressiveness on firm value in technology and digital companies, and to examine the role of Good Corporate Governance (GCG) as a moderating variable. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method using SmartPLS software. The data used are secondary data obtained from financial statements and annual reports of companies listed on the Indonesia Stock Exchange (IDX), with a sampling technique using purposive sampling according to research criteria. The tax aggressiveness variable is measured using the Effective Tax Rate (ETR), firm value is measured by Price to Book Value (PBV) or Tobin's Q, while GCG is proxied by institutional ownership, independent commissioners, and audit committees. The results of the study indicate that tax aggressiveness has an influence on firm value, both positively and negatively depending on investor perceptions and the level of risk posed. In addition, Good Corporate Governance (GCG) has been proven to moderate the relationship between tax aggressiveness and firm value, where good GCG implementation can strengthen the positive influence and minimize the negative impact of tax aggressiveness. This research suggests that companies need to balance tax efficiency strategies with the implementation of good corporate governance to sustainably increase company value.